IJCM_13A: Effect of video based educational intervention in Gestational diabetic mothers on breast feeding self efficacy: a Randomized Control Trial - Mallya Shreya Y; Rao Suchetha S (Wolters Kluwer Medknow Publications, 2024)
Background: Women with Gestational diabetes mellitus face a lot of challenges when it comes to breast feeding. Breast feeding self efficacy is an important factor for improving breast feeding outcomes. Objectives: To know the effect of educational intervention on breast feeding efficacy in immediate postpartum period among women with gestational diabetic mellitus using breast feeding self-efficacy scale short form (BSES-SF). Methodology: A randomized control trial was conducted between May 2022 to August 2023 in a tertiary care hospital in Mangalore. Ethics committee approval was obtained. Clinical trial registry was done (CTRI/2023/03/051176). 108 women with Gestational diabetes mellitus were enrolled in this study. Study participants were divided into control and intervention group. Intervention group were shown an informative video on breast feeding practices and techniques while both the groups were educated using flipcharts on essential newborn care. Breast feeding efficacy was scored in both the groups at admission, after intervention within 48 hours puerperium using breast feeding self-efficacy scale short form (BSES-SF) and results were analyzed. Results: The mean age group of the study was 30.15 ± 5.12. The demographic details in both the groups were comparable. The mean BSES-SF scores were 45.13 pre-intervention vs 55.15 post-intervention in the intervention group (p = <0.001) while mean BSES-SF scores were 44.60 pre-intervention vs 47.53 post-intervention in control group (p = <0.001). Conclusion: Video based educational intervention had a positive impact on breast feeding efficacy in women with Gestational Diabetes Mellitus.